Inventarisasi Dan Keanekaragaman Tumbuhan HerbaPada Ketinggian Yang Berbeda Di Kawasan Hutan AlamGirimanik Desa Setren Wonogiri - Royani, Ina; , Dra. Titik Suryani, M.Sc (2016)
Girimanik Natural Forest is the one of forest which located in low mountains with the height is 2500 m.a.s.l. Biodiversity of plant with high level dominate in region of natural forest which located in Setren, Slogohimo, Wonogiri. The purpose of this research was to know plant species of Herba on height 1400 m.a.s.l. and 1600 m.a.s.l. and to know biodiversity of plant index (H) and species domination index (C) Herba. The method of this research was exploration method and random plot sampling. The result of this research showed there are 12 orders, 12 families, 22 genus that contains 22 species of Herba at height 1400 m.a.s.l. and 1600 m.a.s.l. in Girimanik Natural Forest. The dominant family is Poaceae on height 1400 m.a.s.l. The highest of surface, the biodiversity level is less.